Design and preparation method of high-strength low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy

By combining physical metallurgy models with machine learning to design a β-type medical titanium alloy with low elastic modulus, and through deformation and aging treatment, the problem of high elastic modulus of biomedical titanium alloys is solved, and an efficient and low-cost alloy design is achieved. A high-strength low-modulus titanium alloy with a ratio of strength to elastic modulus is obtained, which avoids the "stress shielding effect" and broadens the application field.

CN119144855AActive Publication Date: 2024-12-17NORTHEASTERN UNIV CHINA

Patent Information

Application Number
CN202411138037.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-17
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The elastic modulus of biomedical titanium alloys is high, resulting in mismatch with human bones, increasing the risk of "stress shielding effect". The development cycle of traditional component design methods is long and costly.

Method used

Using a low-elastic modulus medical titanium alloy design method that integrates physical metallurgy models and machine learning, a high-strength, low-modulus β-type medical titanium alloy is developed in Ti-Mo-Nb-Zr-Sn series alloy through deformation aging treatment. , XGBoost regression model is used to predict alloy components, and the alloy components are optimized through genetic algorithms, combining cold rolling and deformation aging treatment to reduce the elastic modulus of the alloy.

Benefits of technology

Designing multi-alloys that meet specific properties in a shorter time reduces the cost of alloy development and improves design efficiency. The obtained alloy has a lower elastic modulus and higher tensile strength, and the ratio of strength to elastic modulus in the range of modulus in the range of 300000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000 Close to human bones, avoiding the "stress shielding effect" and broadening the application field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144855A_ABST
    Figure CN119144855A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy materials, in particular to a design and preparation method of a high-strength low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy. Beta-type medical titanium alloy with low elastic modulus is designed by adopting a method of combining a physical metallurgical model and machine learning, a titanium alloy plate is prepared through cold working deformation, and finally, the cold-rolled plate is further strengthened by adopting short-time low-temperature deformation aging treatment. The Ti-Mo-Nb-Zr-Sn alloy obtained through the method has the excellent performance of high strength and low modulus, the tensile strength Rm is not lower than 775 MPa, the elastic modulus E is not higher than 45 GPa, the highest strength-modulus ratio is 22.2 * 10 <-3 >, from the aspect of the strength-modulus ratio, on the basis of the low elastic modulus, the mechanical compatibility of the alloy is remarkably improved through deformation aging treatment, the performance requirement is met, and meanwhile the mechanical property of the alloy is improved. The stress shielding phenomenon can be effectively improved, and the material can be used as a potential medical fixing material in clinical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, and in particular to a design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy. Background Art

[0002] Titanium and titanium alloys have high specific strength, good corrosion resistance, excellent biocompatibility and low elastic modulus, so they are widely used in orthopedic implant materials such as artificial joints, spinal orthopedic internal fixation systems, and dental implants. The development of medical titanium alloys has gone through three stages. The first generation of medical titanium alloys is pure titanium and Ti-6Al-4V; the second generation includes α+β type titanium alloys represented by Ti-6Al-7Nb, but Al and V are cytotoxic and can cause malignant tissue reactions. In addition, the elastic modulus of the first and second generation medical titanium alloys is much higher than that of human bones (10-30GPa), resulting in a mismatch between the elastic modulus of implant materials and human bones, which is easy to cause a "stress shielding effect". Long-term implantation in the human body will cause secondary damage to patients. Therefore, in order to meet the clinical demand for medical implant materials, it is extremely important to develop a third-generation β-type medical titanium alloy with better biocompatibility and mechanical properties.

[0003] At present, the traditional semi-quantitative method of alloying and designing medical titanium alloys can no longer quickly achieve accurate design of components, resulting in a lot of trial and error, verification, trial and error, and re-verification, which is time-consuming and economically expensive. The Chinese invention patent (publication number CN115410670A) has a biomedical titanium alloy with excellent elastic modulus and its construction and preparation method, which is characterized by combining big data training and design of machine learning as a theoretical guidance basis, and successfully constructing a Ti with a full β grain structure through big data analysis and learning combined with experiments. 54 Zr 18-x-y Nb 13+x Mo 15+y Biomedical titanium alloys with low elastic modulus break the traditional trial-and-error method of preparing alloys and obtain a reliable alloy composition range in a shorter time.

[0004] A Chinese invention patent (publication number CN116590551A) discloses a high-strength, low-modulus Ti-Nb-Zr biomedical titanium alloy and its preparation method. The main feature of the patent is that the deformation during cold working is controlled to be greater than 90%, thereby reducing the elastic modulus of the alloy and increasing the tensile strength of the alloy. However, its elastic modulus is still much higher than that of human bones, and the "strength-to-modulus ratio (ratio of tensile strength to elastic modulus)" of the alloy has not been significantly improved.

[0005] A Chinese invention patent (publication number CN111676407B) discloses a high-strength, low-elastic modulus medical implant zirconium alloy and a preparation method. The main feature of this patent is that through aging treatment, the alloy precipitates an α phase with a significant dispersion strengthening effect in the low-modulus β matrix. Although the strength of the alloy can be significantly improved, the high-modulus α phase precipitated during the aging process will also increase the elastic modulus of the alloy. Summary of the invention

[0006] In view of the fact that the current biomedical titanium alloys still have a high elastic modulus, and the traditional composition design methods of medical titanium alloys have a long development cycle and high cost, the purpose of the present invention is to provide a design and preparation method for a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, a low-elastic modulus medical titanium alloy design method that integrates physical metallurgy models and machine learning, and strengthens the low-elastic modulus alloy through deformation aging treatment, and develops a β-type medical titanium alloy with high strength and low modulus in the Ti-Mo-Nb-Zr-Sn alloy.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] A design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy is carried out according to the following steps:

[0009] (1) Collect existing literature to create a low elastic modulus medical titanium alloy dataset. The alloy composition (C i ) as input, elastic modulus (E) as output, and Mo equivalent and valence electron concentration, which characterize the stability of β-phase structure, are embedded into the data set as characteristic parameters;

[0010] (2) Establish E = f(C i ) is used to predict the elastic modulus of Ti-Mo-Nb-Zr-Sn alloys;

[0011] (3) Construct the composition space of low modulus alloys, add three physical metallurgical models of Mo equivalent, valence electron concentration and d-electron theory to constrain the composition and phase composition of the alloy at the same time, where: [Mo eq ] is 13 to 15, 2.84~2.90 is 2.40-2.46, e / a is 4.20-4.24;

[0012] (4) Encoding the alloy population that satisfies the three constraints simultaneously with the help of a genetic algorithm, calculating the fitness of each alloy based on the predicted value of the elastic modulus of the alloy, and finding the optimal composition that satisfies the conditions after no more than 400 iterations;

[0013] (5) melting a titanium alloy ingot according to the alloy composition predicted by the machine learning method, wherein the chemical composition by mass percentage is: Mo: 0-4.5%, Nb: 23.5-37.5%, Zr: 0-2.9%, Sn: 0-2.5%, and the rest is Ti;

[0014] (6) According to the composition of the titanium alloy, Ti, Mo, Nb, Zr and Sn are used as raw materials to prepare the components in proportion, smelt them in a vacuum non-consumable arc furnace, turn them over 4 to 5 times, obtain a titanium alloy ingot, and keep it at 1000 to 1200° C. for 2 to 4 hours in a high-purity Ar gas environment;

[0015] (7) hot rolling the titanium alloy ingot after keeping it at 800° C. for 5 to 10 minutes, performing intermediate annealing in each pass, controlling the total deformation of hot rolling to be 75 to 85%, and obtaining a hot-rolled plate;

[0016] (8) The hot-rolled sheet is surface-polished to control the roughness Ra to be above 1.6, the cold-rolled deformation is controlled to be 60-80%, and the deformation during a single cold-rolling process is controlled to be 0.5-2%, thereby obtaining a cold-rolled sheet.

[0017] The method for designing and preparing the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy comprises, in step (1), collecting existing literature to create a low elastic modulus medical titanium alloy data set, which contains 75 different alloy compositions and their corresponding elastic moduli in solid solution, and converting the alloy composition (C i ) as input, elastic modulus (E) as output, and the XGBoost regression model is introduced to establish E = f (C i ), R 2 The closer the value is to 1, the better the model fits the data, the smaller the error, and the higher the accuracy. 2 The values ​​are all above 0.95.

[0018] In the design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, in step (3), three physical metallurgical models, namely, Mo equivalent, valence electron concentration and d-electron theory, are added to constrain the composition and phase composition of the alloy at the same time, and the optimization constraints are as follows:

[0019] Minimize E(a,b,c,d,e)

[0020] Subject to GA(a,b,c,d,e)

[0021] 13.0≤[Mo eq ](a,b,c,d,e)≤15.0

[0022]

[0023] 4.20≤e / a(a,b,c,d,e)≤4.24

[0024] Where a, b, c, d, e represent the contents of Ti, Mo, Nb, Zr, and Sn in the Ti-Mo-Nb-Zr-Sn alloy system; E(a, b, c, d, e) is the predicted value of the elastic modulus of the Ti-Mo-Nb-Zr-Sn alloy designed under the constraints of the optimization model; GA(a, b, c, d, e) is the optimal alloy composition selected by combining with genetic algorithm optimization under the guidance of three physical metallurgical models; [Mo eq ](a,b,c,d,e) is the Mo equivalent value corresponding to the alloy; e / a(a,b,c,d,e) is the average valence electron concentration ratio corresponding to the alloy; and is the d-electron theory corresponding to the alloy Value and value.

[0025] In the design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, in step (8), the cold-rolled alloy phase composition of the cold-rolled plate is β+α″ phase, and by volume percentage, the β phase accounts for 90-93% and the α″ phase accounts for 7-10%.

[0026] The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, in step (8), the cold-rolled plate is subjected to a deformation aging treatment in a high-purity Ar gas environment at 350-450°C for 10-40 minutes to obtain a finished biomedical titanium alloy plate.

[0027] The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy is that the phase composition of the biomedical titanium alloy finished plate deformation-aging alloy is β+α phase, and by volume percentage, the β phase accounts for 95-97% and the α phase accounts for 3-5%.

[0028] The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, the final performance of the biomedical titanium alloy finished plate is: tensile strength R m Not less than 775MPa, elastic modulus E not higher than 45GPa, elongation At not less than 10%, "strength-to-modulus ratio" not less than 20.0×10 -3 .

[0029] The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, in step (8), the cold-rolled plate is solution treated at 750-850°C in a high-purity Ar gas environment for 1-1.5 hours and then water-cooled to room temperature to verify the phase composition and elastic modulus of the titanium alloy.

[0030] In the design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, the solid solution alloy of the cold-rolled plate has a full β grain structure and a grain size of 30 to 50 μm.

[0031] Compared with the current existing technology, the present invention has the following beneficial technical effects:

[0032] 1. The four elements Mo, Nb, Zr and Sn added in the composition design of the present invention are all β-stabilizing elements, and have good biocompatibility with human tissues, will not cause complications, and have an elastic modulus equivalent to that of human bones, which can effectively avoid the "stress shielding effect".

[0033] 2. The present invention breaks the traditional trial-and-error design idea of ​​preparing alloys. Under the theoretical guidance of physical metallurgical principles and combined with big data training of machine learning, multi-component alloys with specific properties can be designed in a shorter time, thereby reducing the cost of alloy development and improving the design efficiency of alloys.

[0034] 3. The phase composition constraints added in the composition design of the present invention can obtain a full β-phase structure with strong phase stability. Within a certain composition range, the alloy will not precipitate a second phase after quenching to deteriorate the elastic modulus of the alloy, and there is a certain degree of tolerance for actual production deviations from the designed composition.

[0035] 4. The present invention adopts a strengthening method of deformation aging treatment, which causes reverse martensitic phase transformation to transform the α″ phase produced during cold rolling into a β phase with a low elastic modulus and a small amount of nanoscale α phase, thereby improving its strength while maintaining a low elastic modulus. The modulus of the alloy obtained after strengthening is close to that of human bone, and can be used as a bone transplant or medical device.

[0036] 5. The preparation method of a high-strength and low-modulus biomedical titanium alloy provided by the present invention greatly improves the development efficiency of the alloy. By using machine learning to design medical titanium alloys, the alloy design cost is reduced while the prepared alloy has both a lower elastic modulus and a higher tensile strength, thereby improving the biomechanical properties of β-type medical titanium alloys and further broadening their application areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a flow chart of the method for designing a high-strength and low-modulus biomedical titanium alloy.

[0038] Figure 2 This is the fitting result of the modeling using the XGBoost (Extreme Gradient Boosting) algorithm in the present invention. In the figure, the horizontal axis Experimental E is the elastic modulus of the experiment (GPa), and the vertical axis Predicted E by XGB is the elastic modulus predicted by XGBoost (GPa); Train is the training set, test is the test set, RMSE is the root mean square error, R 2 is the determination coefficient.

[0039] Figure 3 This is an iterative optimization evolution diagram of the genetic algorithm embedded with physical metallurgical constraints in the present invention. In the figure, the horizontal axis Generation is generation by generation, the vertical axis E elastic modulus (GPa), the Best Objective Value is the best objective value, and the Average Objective Value is the average objective value.

[0040] Figure 4 This is the EBSD phase composition distribution diagram of the solid solution alloy in Example 1.

[0041] Figure 5 This is the EBSD phase composition distribution diagram of the deformation-aged alloy in Example 1.

[0042] Figure 6 : is the engineering stress-strain curve of the solid solution alloy in Example 1. In the figure, the abscissa EngineeringStrain is the engineering strain (%), and the ordinate Engineering Stress is the engineering stress (MPa).

[0043] Figure 7 : This is the engineering stress-strain curve of the deformation-aged alloy in Example 1. In the figure, the abscissa Engineering Strain is the engineering strain (%), and the ordinate Engineering Stress is the engineering stress (MPa).

[0044] Figure 8 The engineering stress-strain curves of the alloys in the solid solution state and the deformation-aging state in Example 2. In the figure, the abscissa Engineering Strain is the engineering strain (%), and the ordinate Engineering Stress is the engineering stress (MPa).

[0045] Fig. 9The engineering stress-strain curves of the alloys in the solid solution state and the deformation-aging state in Example 3. In the figure, the abscissa Engineering Strain is the engineering strain (%), and the ordinate Engineering Stress is the engineering stress (MPa). DETAILED DESCRIPTION

[0046] In the specific implementation process, Figure 1 As shown, the present invention proposes a design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy, and the process includes two parts:

[0047] The first part is to design the composition of low elastic modulus medical titanium alloy based on machine learning method. This part is carried out according to the following steps:

[0048] 1. Establish the original data set and determine the feature parameters

[0049] Based on the existing literature, a Ti-Mo-Nb-Zr-Sn low elastic modulus β-type medical titanium alloy dataset was created. The output parameters in the dataset are all experimental values ​​of the elastic modulus of the sample alloy in the solid solution state. Its phase composition is a single β phase or a β matrix containing a small amount of α″ phase, and they are all obtained by rapid cooling after solid solution treatment, ensuring the accuracy of the dataset samples.

[0050] like Figure 2 As shown, the Mo equivalent [Mo eq ] value and valence electron concentration e / a value are embedded into the dataset as characteristic parameters, and the dataset is randomly divided into training set and test set in a ratio of 9:1, that is, 90% of the data is used to train each model, and 10% of the data is used to detect the prediction performance of the model. Considering that the dataset is a small sample problem, the 10-fold cross-validation method is used to randomly divide the dataset 500 times, and use them as training set and test set in turn to ensure full utilization of the data.

[0051] 2. XGBoost model predicts target value (elastic modulus)

[0052] like Figure 2 As shown in the figure, RMSE and R 2 The statistical values ​​of the model are used to adjust the hyperparameters. After grid search and parameter adjustment, the XGBoost algorithm is used to establish a machine learning model, and the RMSE and R 2 The elastic modulus model is evaluated. In the present invention, the R 2 The values ​​are all above 0.95.

[0053] 3. Add physical metallurgical constraints and create an initial population

[0054] In Ti-Mo-Nb-Zr-Sn alloy, three physical metallurgical constraints on the phase composition and composition of the alloy are added: Mo equivalent value [Mo eq ]:13.0~15.0、Average valence electron concentration ratio e / a:4.20~4.24、Average bond order 2.84~2.90, average d electron orbital energy level 2.40~2.46, and the alloys that meet the constraints are taken as the initial population.

[0055] 4. Predict elastic modulus and determine alloy composition

[0056] like Figure 3 As shown in the figure, the elastic modulus prediction value of the initial population is determined by the XGBoost prediction model, and the fitness of each alloy is calculated according to the elastic modulus value of the alloy in the created initial population. Then, the genetic algorithm is used to find the composition range of alloy Ti, Mo, Nb, Zr, and Sn when the elastic modulus is minimum.

[0057] The chemical composition of the alloy predicted by the machine learning method is, by mass percentage, Mo: 0-4.5%, Nb: 23.5-37.5%, Zr: 0-2.9%, Sn: 0-2.5%, and the rest is Ti; among which: Mo is preferably 0.5-4.5%, Zr is preferably 0.5-2.9%, and Sn is preferably 1.0-2.5%.

[0058] The second part is to prepare the Ti-Mo-Nb-Zr-Sn low modulus alloy that meets the constraints, prepare the alloy ingots by vacuum arc furnace melting and cold deformation, and strengthen it on the basis of low modulus through deformation aging treatment. At the same time, the alloy microstructure phase composition analysis and performance testing are completed to obtain a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy.

[0059] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0060] Example 1

[0061] In this embodiment, a design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy specifically includes the following steps:

[0062] 1. The alloy sample was prepared by using a non-consumable vacuum melting furnace according to the designed composition, and its composition by weight percentage was Mo: 0.5%, Nb: 36.5%, Zr: 0.8%, Sn: 1.6%, and the rest was Ti.

[0063] 2. Alloy smelting: Use pure metal Ti (purity 99.99wt%), Mo (purity 99.99wt%), Nb (purity 99.95wt%), Zr (purity 99.99wt%) and Sn (purity 99.95wt%) as raw materials, and adopt a non-consumable vacuum arc furnace to melt them into button ingots. Turn on the current to strike the arc and repeatedly turn the button ingot over and melt it 5 times to ensure the uniform composition of the alloy.

[0064] 3. The button ingots cast after smelting are homogenized, and the button ingots are kept at 1000° C. for 2 h in a high-purity Ar gas (volume purity 99.9999%, the same below) environment and then water-cooled to room temperature.

[0065] 4. The button ingot is hot rolled after being kept at 800℃ for 10min, with intermediate annealing in each pass. The total deformation of hot rolling is 80%.

[0066] 5. After the hot-rolled sheet is cooled to room temperature, the hot-rolled sheet is rolled on a cold rolling mill for multiple passes, with an average pass reduction of 1.5% and a final reduction of 60%. The cold-rolled alloy phase composition of the cold-rolled sheet is β+α″ phase, in which the β phase accounts for 93% and the α″ phase accounts for 7% by volume.

[0067] 6. Two groups of heat treatments were performed on the cold-rolled plates: one group was subjected to solid solution treatment to verify the phase composition and elastic modulus of the alloy, and the cold-rolled plates were kept at 800°C for 1 hour in a high-purity Ar gas environment and then water-cooled to room temperature; the other group was subjected to deformation aging treatment, and the cold-rolled plates were kept at 400°C for 20 minutes in a high-purity Ar gas environment and then water-cooled to room temperature, and finally the finished medical titanium alloy plates with both high strength and low modulus were obtained.

[0068] 7. Pass Figure 4 The phase composition analysis shows that the phase composition of the solid solution Ti-0.5Mo-36.5Nb-0.8Zr-1.6Sn alloy is mainly green equiaxed β phase, with no second phase precipitation, and its average grain size is about 37μm, which meets the added phase composition constraints. Figure 5 The phase composition results show that after deformation aging treatment, the strength of the alloy can be significantly improved under the combined effect of fine grains and the second phase. At the same time, due to the short aging time, the reverse martensitic phase transformation occurs, causing the α″ phase produced during the cold rolling process to transform into a β phase with a low elastic modulus and a small amount of nanoscale α strengthening phase. By volume percentage, the β phase accounts for 97% and the α phase accounts for 3%, which has little effect on the elastic modulus.

[0069] 8. The samples were subjected to room temperature tensile tests using an AG-X plus 100kN universal tensile testing machine. The tensile rate during the test was 0.5mm / min. An extensometer was installed during the experiment to accurately measure the change in gauge displacement. In order to ensure the reliability of the experiment, three parallel samples were prepared for tensile testing, and the average of the test results was taken as the final result of the mechanical properties.

[0070] 9. Pass Figure 6 The stress-strain curve results of the solid solution alloy show that the yield strength R p0.2 The tensile strength is 428MPa and R m According to Hooke's law, the slope in the elastic deformation stage is the elastic modulus of the alloy. In this embodiment, the experimental value E of the elastic modulus of the alloy is 35 GPa, which is close to the elastic modulus of human bones and is consistent with the predicted value of the elastic modulus of 38 GPa.

[0071] 10. From Figure 7 It can be seen from the stress-strain curve of the deformation aging state that, compared with the solid solution state, the alloy achieves a good combination of high strength and low modulus after cold rolling and aging at 400℃ for 20min. p0.2 The tensile strength is 685MPa and R m 778 MPa, elastic modulus E is 35 GPa, elongation At is 10.1%, and "strength-to-modulus ratio" is 22.2×10 -3 .

[0072] Example 2

[0073] In this embodiment, a design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy specifically includes the following steps:

[0074] 1. The alloy sample was prepared by using a non-consumable vacuum melting furnace according to the designed composition, and its composition by weight percentage was Mo: 4.2%, Nb: 24.6%, Zr: 2.9%, and the rest was Ti.

[0075] 2. Alloy smelting: Use pure metal Ti (purity 99.99wt%), Mo (purity 99.99wt%), Nb (purity 99.95wt%) and Zr (purity 99.99wt%) as raw materials, and adopt a non-consumable vacuum arc furnace to melt them into button ingots. Turn on the current to strike the arc and repeatedly turn the button ingot over and melt it 5 times to ensure the uniform composition of the alloy.

[0076] 3. The button ingots cast after smelting are homogenized, kept at 1000°C for 2 hours in a high-purity Ar gas environment, and then water-cooled to room temperature.

[0077] 4. The button ingot is hot rolled after being kept at 800℃ for 10min, with intermediate annealing in each pass. The total deformation of hot rolling is 80%.

[0078] 5. After the hot-rolled sheet is cooled to room temperature, the hot-rolled sheet is rolled on a cold rolling mill for multiple passes, with an average pass reduction of 1% and a final reduction of 80%. The cold-rolled alloy phase composition of the cold-rolled sheet is β+α″ phase, with β phase accounting for 90% and α″ phase accounting for 10% by volume.

[0079] 6. Two groups of heat treatments were performed on the cold-rolled plates: one group was subjected to solid solution treatment to verify the phase composition and elastic modulus of the alloy, and the cold-rolled plates were kept at 800°C for 1 hour in a high-purity Ar gas environment and then water-cooled to room temperature; the other group was subjected to deformation aging treatment, and the cold-rolled plates were kept at 450°C for 30 minutes in a high-purity Ar gas environment and then water-cooled to room temperature, and finally the finished medical titanium alloy plates with both high strength and low modulus were obtained.

[0080] 7. The solid solution Ti-4.2Mo-24.6Nb-2.9Zr alloy is a full β phase of equiaxed grains, which meets the phase composition constraints and has an average grain size of about 32μm. After deformation aging treatment, the alloy has a phase composition of matrix β phase and a small amount of α phase. By volume percentage, β phase accounts for 95% and α phase accounts for 5%, which has little effect on the elastic modulus.

[0081] 8. The samples were subjected to room temperature tensile tests using an AG-X plus 100kN universal tensile testing machine. The tensile rate during the test was 0.5mm / min. An extensometer was installed during the experiment to accurately measure the change in gauge displacement. In order to ensure the reliability of the experiment, three parallel samples were prepared for tensile testing, and the average of the test results was taken as the final result of the mechanical properties.

[0082] 9. Pass Figure 8 The stress-strain curve results of the solid solution alloy show that the yield strength R p0.2 The tensile strength is 448MPa and R m According to Hooke's law, the slope in the elastic deformation stage is the elastic modulus of the alloy. In this embodiment, the experimental value E of the elastic modulus of the alloy is 40 GPa, which is close to the elastic modulus of human bones and is consistent with the predicted value of the elastic modulus of 43 GPa.

[0083] 10. From Figure 8 It can be seen from the stress-strain curve of the deformation aging state that compared with the solid solution state, the alloy achieves a good combination of high strength and low modulus after cold rolling and aging at 450℃ for 30min. p0.2 The tensile strength is 732MPa and R mThe elastic modulus E is 921MPa, the elongation At is 10.4%, and the strength-to-modulus ratio is 21.9×10 -3 .

[0084] Example 3

[0085] In this embodiment, a design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy specifically includes the following steps:

[0086] 1. The alloy sample was prepared by using a non-consumable vacuum melting furnace according to the designed composition, and its composition by weight percentage was Mo: 3.3%, Nb: 29.0%, Sn: 2.1%, and the rest was Ti.

[0087] 2. Alloy smelting uses pure metal Ti (purity 99.99wt%), Mo (purity 99.99wt%), Nb (purity 99.95wt%) and Sn (purity 99.95wt%) as raw materials and adopts a non-consumable vacuum arc furnace to melt them into button ingots. The current is turned on to strike the arc and the button ingots are repeatedly turned over and melted 5 times to ensure the uniform composition of the alloy.

[0088] 3. The button ingots cast after smelting are homogenized, kept at 1000°C for 2 hours in a high-purity Ar gas environment, and then water-cooled to room temperature.

[0089] 4. The button ingot is hot rolled after being kept at 800℃ for 10min, with intermediate annealing in each pass. The total deformation of hot rolling is 80%.

[0090] 5. After the hot-rolled sheet is cooled to room temperature, the hot-rolled sheet is rolled on a cold rolling mill for multiple passes, with an average pass reduction of 2% and a final reduction of 80%. The cold-rolled alloy phase composition of the cold-rolled sheet is β+α″ phase, with β phase accounting for 91% and α″ phase accounting for 9% by volume.

[0091] 6. Two groups of heat treatments were performed on the cold-rolled plates: one group was subjected to solid solution treatment to verify the phase composition and elastic modulus of the alloy, and the cold-rolled plates were kept at 800°C for 1 hour in a high-purity Ar gas environment and then water-cooled to room temperature; the other group was subjected to deformation aging treatment, and the cold-rolled plates were kept at 400°C for 20 minutes in a high-purity Ar gas environment and then water-cooled to room temperature, and finally the finished medical titanium alloy plates with both high strength and low modulus were obtained.

[0092] 7. The solid solution Ti-3.3Mo-29.0Nb-2.1Sn alloy is a full β phase of equiaxed grains, which meets the phase composition constraints and has an average grain size of about 42μm. After deformation aging treatment, the alloy has a phase composition of matrix β phase and a small amount of nanoscale α phase. By volume percentage, β phase accounts for 95% and α phase accounts for 5%, which has little effect on the elastic modulus.

[0093] 8. The samples were subjected to room temperature tensile tests using an AG-X plus 100kN universal tensile testing machine. The tensile rate during the test was 0.5mm / min. An extensometer was installed during the experiment to accurately measure the change in gauge displacement. In order to ensure the reliability of the experiment, three parallel samples were prepared for tensile testing, and the average of the test results was taken as the final result of the mechanical properties.

[0094] 9. Pass Fig. 9 The stress-strain curve results of the solid solution alloy show that the yield strength R p0.2 The tensile strength is 451MPa and R m According to Hooke's law, the slope in the elastic deformation stage is the elastic modulus of the alloy. In this embodiment, the experimental value E of the elastic modulus of the alloy is 42 GPa, which is close to the elastic modulus of human bones and is consistent with the predicted value of the elastic modulus of 45 GPa.

[0095] 10. From Fig. 9 It can be seen from the stress-strain curve of the deformation aging state that compared with the solid solution state, the alloy achieved a good combination of high strength and low modulus after cold rolling and aging at 350℃ for 40min. p0.2 The tensile strength is 771MPa and the tensile strength is R m The elastic modulus E is 908MPa, the elongation At is 11.1%, and the strength-to-modulus ratio is 20.2×10 -3 .

[0096] The implementation results show that the present invention uses a combination of physical metallurgical model and machine learning to design a β-type medical titanium alloy with low elastic modulus in Ti-Mo-Nb-Zr-Sn alloy, prepares titanium alloy sheets by cold working deformation, and finally further strengthens the cold-rolled sheets by short-term and low-temperature deformation aging treatment. The Ti-Mo-Nb-Zr-Sn alloy prepared by the method of the present invention has excellent properties of high strength and low modulus, and the tensile strength R m Not less than 775MPa, elastic modulus E not higher than 45GPa, elongation At not less than 10%, "strength-to-modulus ratio" up to 22.2×10 -3 From the perspective of "strength-to-modulus ratio", on the basis of low elastic modulus, deformation aging treatment significantly improves the mechanical compatibility of the alloy. While meeting the performance requirements, it can also effectively improve the "stress shielding phenomenon" and can be used as a potential medical fixation material in clinical applications.

Claims

1. A design and preparation method of a high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy. It is characterized in that Follow these steps: (1) Collect existing literature to create a low elastic modulus medical titanium alloy dataset. The alloy composition (C i ) as input, elastic modulus (E) as output, and Mo equivalent and valence electron concentration, which characterize the stability of β-phase structure, are embedded into the data set as characteristic parameters; (2) Establish E = f(C i ) is used to predict the elastic modulus of Ti-Mo-Nb-Zr-Sn alloys; (3) Construct the composition space of low modulus alloys, add three physical metallurgical models of Mo equivalent, valence electron concentration and d-electron theory to constrain the composition and phase composition of the alloy at the same time, where: [Mo eq ] is 13 to 15, 2.84~2.90 is 2.40-2.46, e / a is 4.20-4.24; (4) Encoding the alloy population that satisfies the three constraints simultaneously with the help of a genetic algorithm, calculating the fitness of each alloy based on the predicted value of the elastic modulus of the alloy, and finding the optimal composition that satisfies the conditions after no more than 400 iterations; (5) melting a titanium alloy ingot according to the alloy composition predicted by the machine learning method, wherein the chemical composition by mass percentage is: Mo: 0-4.5%, Nb: 23.5-37.5%, Zr: 0-2.9%, Sn: 0-2.5%, and the rest is Ti; (6) According to the composition of the titanium alloy, Ti, Mo, Nb, Zr and Sn are used as raw materials to prepare the components in proportion, smelt them in a vacuum non-consumable arc furnace, turn them over 4 to 5 times, obtain a titanium alloy ingot, and keep it at 1000 to 1200° C. for 2 to 4 hours in a high-purity Ar gas environment; (7) hot rolling the titanium alloy ingot after keeping it at 800° C. for 5 to 10 minutes, performing intermediate annealing in each pass, controlling the total deformation of hot rolling to be 75 to 85%, and obtaining a hot-rolled plate; (8) The hot-rolled sheet is surface-polished to control the roughness Ra to be above 1.6, the cold-rolled deformation is controlled to be 60-80%, and the deformation during a single cold-rolling process is controlled to be 0.5-2%, thereby obtaining a cold-rolled sheet.

2. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 1, It is characterized in that In step (1), existing literature was collected to create a low elastic modulus medical titanium alloy dataset, which contains 75 different alloy compositions and their corresponding elastic moduli in solid solution state, and the alloy composition (C i ) as input, elastic modulus (E) as output, and the XGBoost regression model is introduced to establish E = f (C i ), R 2 The closer the value is to 1, the better the model fits the data, the smaller the error, and the higher the accuracy. 2 The values ​​are all above 0.

95.

3. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 1, It is characterized in that In step (3), three physical metallurgical models, namely, Mo equivalent, valence electron concentration and d-electron theory, are added to constrain the composition and phase composition of the alloy. The optimization constraints are as follows: Minimize E(a,b,c,d,e) Subject to GA(a,b,c,d,e) 13.0≤[Mo eq ](a,b,c,d,e)≤15.0 4.20≤e / a(a,b,c,d,e)≤4.24 Where a, b, c, d, e represent the contents of Ti, Mo, Nb, Zr, and Sn in the Ti-Mo-Nb-Zr-Sn alloy system; E(a, b, c, d, e) is the predicted value of the elastic modulus of the Ti-Mo-Nb-Zr-Sn alloy designed under the constraints of the optimization model; GA(a, b, c, d, e) is the optimal alloy composition selected by combining with genetic algorithm optimization under the guidance of three physical metallurgical models; [Mo eq ](a,b,c,d,e) is the Mo equivalent value corresponding to the alloy; e / a(a,b,c,d,e) is the average valence electron concentration ratio corresponding to the alloy; and is the d-electron theory corresponding to the alloy Value and value.

4. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 1, It is characterized in that In step (8), the cold-rolled alloy phase composition of the cold-rolled sheet is β+α″ phase, in which the β phase accounts for 90-93% and the α″ phase accounts for 7-10% by volume.

5. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 1, It is characterized in that In step (8), the cold-rolled sheet is subjected to a deformation aging treatment in a high-purity Ar gas environment at 350 to 450° C. for 10 to 40 minutes to obtain a finished biomedical titanium alloy sheet.

6. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 5, It is characterized in that The phase composition of the biomedical titanium alloy finished plate in the deformation-aging state is β+α phase, in which the β phase accounts for 95-97% and the α phase accounts for 3-5% by volume.

7. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 5 or 6, It is characterized in that The final properties of the finished biomedical titanium alloy plate are: tensile strength R m Not less than 775MPa, elastic modulus E not higher than 45GPa, elongation At not less than 10%, "strength-to-modulus ratio" not less than 20.0×10 -3 .

8. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 1, It is characterized in that In step (8), the cold-rolled plate is solution treated at 750-850° C. in a high-purity Ar gas environment for 1-1.5 hours and then water-cooled to room temperature to verify the phase composition and elastic modulus of the titanium alloy.

9. The design and preparation method of the high-strength and low-modulus Ti-Mo-Nb-Zr-Sn biomedical titanium alloy according to claim 8, It is characterized in that The solid solution alloy of the cold rolled sheet has a full β grain structure, and the grain size is 30 to 50 μm.

Citation Information

Patent Citations

  • Low-elasticity-modulus high-fatigue-strength biologic implantable titanium alloy and preparation method thereof

    CN105420549A

  • Medical implanted titanium alloy with low elastic modulus and high fatigue strength and preparation method

    CN107805740A

  • Medical beta-titanium alloy plate and cold machining manufacturing method for controlling texture thereof

    CN113930641A

  • Titanium alloy with high strength and low elastic modulus and preparation method thereof

    CN116024458A

  • High-strength low-modulus Ti-Nb-Zr biomedical titanium alloy and preparation method thereof

    CN116590551A

Cited By

  • Method for preparing titanium alloy with low elastic modulus by recovering residual titanium based on data driving

    CN122484527A